2016
DOI: 10.4037/ajcc2016875
|View full text |Cite
|
Sign up to set email alerts
|

Five-Layered Soft Silicone Foam Dressing to Prevent Pressure Ulcers in the Intensive Care Unit

Abstract: Background In critically ill patients, prevention of pressure ulcers is a challenge because of the high risk for multiple comorbid conditions, immobility, hemodynamic instability, and increased use of medical devices. Objectives To compare the difference in incidence rates of hospital-acquired pressure ulcers (HAPUs) in critically ill patients between those treated with usual preventive care and a 5-layered soft silicone foam dressing versus a control group receiving usual care. Secondary goals were to examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
105
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(116 citation statements)
references
References 51 publications
8
105
2
1
Order By: Relevance
“…In agreement with our previous computational modelling work with regard to the biomechanical function of dressings in PUP, here, we found that application of the dressing cuts considerably reduced peak stresses in facial soft tissues for both model variants BCS1 and BCS2, in comparison with the respective no‐dressing cases. Furthermore, use of the dressing cuts substantially reduced the volumetric exposure of facial soft tissues to elevated effective stresses and SED values, for BCS1 at the bridge of the nose and for BCS2 at the chin.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with our previous computational modelling work with regard to the biomechanical function of dressings in PUP, here, we found that application of the dressing cuts considerably reduced peak stresses in facial soft tissues for both model variants BCS1 and BCS2, in comparison with the respective no‐dressing cases. Furthermore, use of the dressing cuts substantially reduced the volumetric exposure of facial soft tissues to elevated effective stresses and SED values, for BCS1 at the bridge of the nose and for BCS2 at the chin.…”
Section: Discussionsupporting
confidence: 92%
“…26 It is noteworthy that, in the same context of PUP, the Mepilex Border prophylactic dressing designs (Mölnlycke Health Care) have been shown to successfully protect vulnerable tissue sites subjected to sustained bodyweight forces, for example, near the sacrum and calcaneal (heel) bones; their effectiveness in alleviating localised tissue loads has been demonstrated in multiple biomechanical computational studies, as well as in large-scale randomised clinical trials. [27][28][29][30][31][32][33][34][35] The ability to non-invasively monitor changes in skin microcirculation improves both the diagnosis and treatment of certain diseases. It was already observed that cutaneous haemodynamic variables could reflect local and systemic changes and even predict the development of ischemic stress conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In this latter study, which included 77 adults hospitalised at the Mayo Clinic in the United States, it has been demonstrated that the normal trajectory of tissue destruction associated with DTIs was changed, and DTIs healed, through early intervention with the MBS dressing. This provides strong clinical support for the present computational modelling results, demonstrating that the MBS either prevents DTIs or helps DTIs not to deteriorate…”
Section: Discussionsupporting
confidence: 78%
“…Santamaria et al and Cubit et al demonstrated that the use of the multi‐layer silicone foam Mepilex Border Sacrum and Mepilex Heel dressings (Molnlycke Health Care AB, Gothenburg, Sweden) significantly decreased PI incidence in critically ill patients when applied in the ED . The prophylactic use of these dressings has also been shown to decrease overall wound care costs when applied in the ED for critically ill patients …”
Section: Evidence‐based Interventions To Minimise the Development Of mentioning
confidence: 99%
“…45 The prophylactic use of these dressings has also been shown to decrease overall wound care costs when applied in the ED for critically ill patients. [46][47][48] 6 | LEADERSHIP, LOCAL CULTURE, AND MANAGEMENT All levels of senior and unit-based clinical and hospital management have a vital role in the prevention of PIs in the ED. It is the role of senior-level executives to set expectations and support staff to accomplish PI prevention goals, remove barriers, encourage collaboration, and provide the required human and financial resources.…”
Section: Evidence-based Interventions To Minimise the Development Omentioning
confidence: 99%